Depth and type of substrate influence the ability of Nasonia vitripennis to locate a host. Issue 1 (1st January 2014) - Frederickx, Christine; Dekeirsschieter, Jessica; Verheggen, François J.; Haubruge, Eric
Abstract: The foraging behaviour of a parasitoid insect species includes the host's habitat and subsequent location of the host. Habitats substrate, substrate moisture, and light levels can affect the host searching of different species of parasitoids. However, the depth at which parasitoids concentrate their search effort is another important ecological characteristic and plays an important role in locating a host. Here, we investigated the ability of a pupal parasitoid, Nasonia vitripennis Walker (Hymenoptera: Pteromalidae), to penetrate and kill fly pupae located at different depths of the substrate. Three different types of substrate were tested: loam soil, compost, and vermiculite substrate. In both loam soil and compost, all of the parasitism activity was restricted to pupae placed directly on the surface. Parasitism activity in vermiculite showed that the average number of pupae parasitized decreased with depth of substrate. These results suggest that fly pupae situated deeper in the substrate are less subjected to parasitism by N. vitripennis .